iSpeechNews:s real time speech news service for ubiquitous computing environment - Mantoro, Teddy; Ayu, Media Anugerah; Jaafar, Abi Dzar (2010)
ir-SpeechNews is a protocol to deliver a real time news service in form of speech news and lips graphics animation based on user location for Ubiquitous Computing Environment. The protocol requires 5 (five) important hybrid stacks, i.e. 1. user identity, 2. user location, 3. a real time news feeder 4. speech and dictations systems and 5. lips synchronization in responding to user activity.